THE INFLUENCE OF MOTORCYCLE ON THE CAPACITY OF TWO LANE TWO WAY UNDIVIDED URBAN ROAD LINKS IN DENPASAR, BALI - Wedagama, D.M Priyantha; Purbanto, I Gusti Raka (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 18, No. 1, Januari 2014, 2016)
The proportion of motorcycle in Denpasar city is accounted for by more than 85%. This indicated that motorcycle dominated traffic flows in Denpasar city. Three types of vehicles consisting motorcycle, heavy and light vehicles make up such a mixed traffic condition. This certainly is potential to create traffic problems involving road capacity reduction. This study investigates the effect of motorcycle on capacity of two lane two way undivided urban roads in Denpasar city. Linear regression models were developed for two separate locations consisting mid blocks of Ahmad Yani Road and Hayam Wuruk Road. The motorcycle percentage on Ahmad Yani Road is less scattered than that on Hayam Wuruk Road. Therefore, the relationship between road capacity and motorcycle percentages on Hayam Wuruk Road (R2 = 0.46) is less significant than that on Ahmad Yani Road (R2 = 0.78). Both locations however, suggest the same results. This study found that road capacity decreases as the percentage of motorcycle in the traffic stream increases. The motorcycle equivalent unit (MEU) therefore, is suggested for future study to convert such a mixed traffic condition into a homogeneous condition.
Keywords: Motorcycle, Road Capacity, Urban Road Links